Sending older parents to the nursing home from the perspective of islamic law - Anwar, Syamsul (Universitas Ahmad Dahlan, 2023)
In Muslim communities, there are nursing homes and elderly care facilities, some of which are operated by Islamic organizations such as Aisyiyah in Indonesia, which is part of Muhammadiyah. The community grapples with the question of how Islamic law views the act of children placing their elderly parents in nursing homes, given that there are differing opinions on this matter. This article investigates the Islamic perspective on this issue. Using a library research approach, it explores whether it is considered disobedient and thus prohibited or whether positive aspects should be considered. The article concludes on several points, namely: (1) Islamic law strongly emphasizes the obligation of honoring the elderly both by the children or their families, as well as by society and the state; (2) It is obligatory for children to do good (iḥsān) to their parents, which is reflected among others in the form of providing them with proper support and maintenance when they are no longer able to be independent. Deliberately neglecting one's parents and avoiding responsibility for their upkeep out of laziness, despite having the economic and social capacity to do so, is a violation of the child's obligation and is a form of disobedience; and (3) Placing one's parents in a nursing home by the child due to social and economic conditions that make it impossible for them to take care of them on their own and with the consideration that the interests of the parents will be better secured and to avoid neglect and on condition that the parents are willing, is permissible. Placing parents in a nursing home is a last resort after other efforts have been exhausted.